2022
DOI: 10.3390/nu14183689
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Processed Foods as Ingredients of Culinary Recipes Shared on Popular Brazilian YouTube Cooking Channels

Abstract: Social media platforms are readily accessible sources of information about cooking, an activity deemed crucial for the improvement of a population’s diet. Previous research focused on the healthiness of the content shared on websites and blogs, but not on social media such as YouTube®. This paper analysed the healthiness of 823 culinary recipes retrieved from 755 videos shared during a six-month period on ten popular Brazilian YouTube® cooking channels. Recipes were categorized by type of preparation. To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…Nevertheless, our study agrees with previous research, where most recipes online were found to be unhealthy according to the World Health Organization and the United Kingdom Food Standards Agency’s recommendations [ 19 ], including those that use a ‘healthy’ appeal in their descriptions [ 19 , 44 , 45 ]. Previous research in the Brazilian context, conducted on YouTube ® and not focused on ‘healthy recipes’, also identified the presence of UP foods as ingredients and a scarcity of fruits, legumes, nuts, and seeds [ 43 ]. Our results help to fill a gap in the literature, revealing not only that the recipes shared as ‘healthy’ deviate from dietary guidelines, but also appeal to diet trends, body image, and physical exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, our study agrees with previous research, where most recipes online were found to be unhealthy according to the World Health Organization and the United Kingdom Food Standards Agency’s recommendations [ 19 ], including those that use a ‘healthy’ appeal in their descriptions [ 19 , 44 , 45 ]. Previous research in the Brazilian context, conducted on YouTube ® and not focused on ‘healthy recipes’, also identified the presence of UP foods as ingredients and a scarcity of fruits, legumes, nuts, and seeds [ 43 ]. Our results help to fill a gap in the literature, revealing not only that the recipes shared as ‘healthy’ deviate from dietary guidelines, but also appeal to diet trends, body image, and physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Weak and general categories were regrouped until strong or terminal categories resulted [ 49 ]. Analysis was carried out both deductively and inductively, starting with pre-defined categories: appetizers; breads; cakes and baked goods; homemade ingredients; meat or egg main dishes; non-alcoholic beverages; preserves; puddings; sauces; savory cakes and pies; salads; savory spreads and pâtés; side dishes; snacks and homemade fast foods; soups and creams; and sweet spreads [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Steils and Obaidalahe (2020) has only considered how individuals themselves contribute to food literacy via commenting on recipes, but did not study how the recipe itself provides information regarding the various Nutritional value of influencers' recipes Furthermore, despite the growing popularity of food influencers on Instagram, there has been limited research evaluating the nutritional value of the recipes they promote. Previous studies have assessed the nutritional quality of recipes from various sources, including cooking television shows, recipe websites and social media platforms such as YouTube and Pinterest (Ngqangashe et al, 2018;Schneider et al, 2013;Camargo et al, 2022;Cheng et al, 2021).…”
Section: References To Food Literacy Aspectsmentioning
confidence: 99%
“…Recipe-related content can display the basic instructions and ingredients needed to prepare a meal or can go beyond and provide additional information regarding meal planning, food selection, preparation and consumption (Herrera, 2021). Previous research has focused on the examination of specific facets of food literacy, such as food safety (Melville et al, 2023;Geppert et al, 2019;Barrett and Feng, 2020;Borda et al, 2014), or the nutritional value of recipes from various media sources (Ngqangashe et al, 2018;Schneider et al, 2013;Camargo et al, 2022;Cheng et al, 2021). However, to our knowledge, an investigation into food influencers' recipes in terms of observing all various aspects of food literacy together as well as examining the nutritional value has not yet been done.…”
Section: Introductionmentioning
confidence: 99%